Weld lines in tow-based sheet moulding compounds tensile properties: Morphological detrimental factors. (December 2020) - Martulli, L.M.; Kerschbaum, Martin; Lomov, Stepan V.; Swolfs, Yentl
Abstract: Weld lines (WLs) are among the most detrimental defects affecting polymer composites. While they have been extensively studied in short fibre composites, their effects on tow-based composites are largely unknown. In this study, tow-based carbon fibre sheet moulding compounds were used to compression mould plates with WLs. Three different WLs configurations were considered: WLs in (1) low-flow moulding, (2) high-flow moulding with opposite meeting fronts and (3) high-flow moulding with adjacent meeting fronts. The tensile strength of the WL specimens was between 48% and 88% of the pristine material. Tows were highly distorted in the region of the WLs, both in-plane and out-of-plane, and a significant tow re-orientation parallel to the WLs was recorded. The meeting flow fronts acted as a physical barrier to each other, preventing tows to intermingle. A comprehensive characterisation of the effects and the main detrimental factors of WLs in tow-based composites was thus presented.